2020
DOI: 10.1111/ans.16202
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular invasion and risk of recurrence in papillary thyroid carcinoma

Abstract: Background Lymphovascular invasion (LVI) is an established adverse prognostic factor in many cancers, however, there are few studies assessing its significance in papillary thyroid carcinoma (PTC). We aimed to determine if LVI is an independent prognostic factor in PTC. Methods We conducted a single institution retrospective analysis of 610 patients with PTC treated between 1987 and 2016. LVI was defined as the presence or absence of cancer cells in blood vessels and/or lymphatics on histopathology. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We also found that the size of cancer >3 cm is an independent risk factor for the persistence of the disease, concordant with reports from previous studies (29)(30)(31). A larger tumor size may have an impact on the relative risk of not being cured (29).…”
Section: Discussionsupporting
confidence: 92%
“…We also found that the size of cancer >3 cm is an independent risk factor for the persistence of the disease, concordant with reports from previous studies (29)(30)(31). A larger tumor size may have an impact on the relative risk of not being cured (29).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the presence of LI in p-PTMCs was related with the presence of LNM. Although the results of some studies suggest an association between LI of PTMC and PTC and the LNM [24,[34][35][36][37], there is general agreement that only the blood vessel invasion has a prognostic value [38]. Vascular and lymphatic endothelial cells immunohistochemical markers were not used in this study to prevent misinterpretation of LI from its histological mimics [36,39] constituting a limitation.…”
Section: Discussionmentioning
confidence: 98%
“…Lymphovascular invasion in thyroid cancer is defined as the movement of cancer cells into the blood vessels and/or lymphatic vessels, as observed in histopathology. 13 In a previous study, Kim and co‐workers confirmed the existence of a significant correlation between lymphatic vessel invasion and lateral neck lymph node metastasis, as revealed by an analysis of 662 patients with papillary thyroid cancer. 14 Meta‐analysis performed by Yoon and co‐workers also showed that lymphovascular invasion was significantly related to metastasis of contralateral cervical lymph nodes, especially in the case of level-III and -IV lymph node.…”
Section: Discussionmentioning
confidence: 83%